Combined Spinal Epidural Technique for Labor Analgesia Does Not Delay Recognition of Epidural Catheter Failures: A Single-center Retrospective Cohort Survival Analysis. Issue 2 (June 2017) - Booth, J.M.; Pan, J.C.; Ross, V.H.; Russell, G.B.; Harris, L.C.; Pan, P.H.
Abstract : ( Anesthesiology. 2016;125(3):516–524) Traditional epidural (EPID) analgesia has long been used for labor analgesia; combined spinal-epidural (CSE) analgesia was initially viewed as a refinement of EPID. Advantages of CSE compared with EPID include faster onset of complete analgesia and a lower incidence of epidural catheter failures. Other possible advantages include a lower incidence of motor blockade and risk of hypotension and reduced duration of first-stage labor in nulliparous parturients. Despite these advantages, most of the current literature and policies recommend using EPID rather than CSE. One reason for this recommendation is the belief that epidural catheter failure will be recognized sooner when analgesia is initiated with an EPID compared with CSE technique. The first several hours of analgesia using CSE rely on the spinal dose; thus the catheter remains "untested." Experts have suggested that CSE should not be used in patients who are at increased risk of requiring urgent cesarean delivery, when the presence of a functioning epidural catheter is important for safe care. These patients include women with severe preeclampsia, history of placental abruption, abnormal fetal presentation, multiple gestation, fetal macrosomia, and patients with difficult airway indices and morbid obesity. However, differences in the timing of catheter failure between CSE and EPID have not yet been studied and there is no evidence to suggest recognition of epidural catheter failures is delayed with CSE compared with EPID.